The pathotype distribution of Puccinia recondita f. sp. tritici in India during 1987-89 - S. C. BHARDWAJ; L. R. VERMA, S.K. NAYAR, M. PRASHAR, J. KUMAR (Indian Phytopathology, 2002)
Pathotype 1048 (29R23) of Puccinia recondita f. sp. tritici, possessing virulence against Lr 23 was predominant followed by 77 (45R31) and 77-A (109R31) which match LrI3, LrI5 and LrI3, LrIO, Lrl5, respectively during 1987 and 1988 crop seasons. Pathotype 77 (45R31) predominated during 1988-89 followed by 77-A-I (109R23) virulent on LrIO, LrI3, LrI5 and 1048(29R23). Four new pathotypes, namely 12-3(49R37), 77-3(125R55) and 107-1(45R35) matching Lr26 and 108-1 (57R27) virulent on Lrl5 were identified during this period. Genes Lr9, LrI9, Lr24, Lr25, Lr28 & L;’29 continued to show resistance to leaf rust. Compared to 1983-86, effectiveness of Lr23 and Lr26 has reduced considerably during 1987-89.